2021
DOI: 10.1177/17455065211042190
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum stress and protective factors in women who gave birth in the United States during the COVID-19 pandemic

Abstract: Objectives: The COVID-19 pandemic has caused considerable stress throughout the world. Little is known about how postpartum women who gave birth during the early months of the pandemic were impacted. The purpose of this study was to explore and describe the associations between potential risk, protective factors, and psychological distress among postpartum women who gave birth during the early months of the COVID-19 pandemic. Methods: Postpartum women over the age of 18 years who gave birth in the US hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 76 publications
2
37
0
3
Order By: Relevance
“…An American mixed-methods study of 16 pregnant and 15 postpartum women reported six times higher levels of prenatal anxiety during the pandemic as compared to previous studies conducted in the Colorado area, and wellbeing and resilience scores were lower than before the pandemic [12]. Another American crosssectional study including 885 women found that participants had higher stress and lower resilience relative to pre-pandemic numbers, and that resilience and mastery were related to lower stress, depression, and anxiety [13]. An Italian cross-sectional study of 163 women found depressive symptoms in 44.2% (using EPDS) of the participants and post-traumatic stress syndrome (PTSS) in 42.9% of them.…”
Section: Introductionmentioning
confidence: 87%
“…An American mixed-methods study of 16 pregnant and 15 postpartum women reported six times higher levels of prenatal anxiety during the pandemic as compared to previous studies conducted in the Colorado area, and wellbeing and resilience scores were lower than before the pandemic [12]. Another American crosssectional study including 885 women found that participants had higher stress and lower resilience relative to pre-pandemic numbers, and that resilience and mastery were related to lower stress, depression, and anxiety [13]. An Italian cross-sectional study of 163 women found depressive symptoms in 44.2% (using EPDS) of the participants and post-traumatic stress syndrome (PTSS) in 42.9% of them.…”
Section: Introductionmentioning
confidence: 87%
“…Though a phase of nourishment, enrichment, and amelioration, the postpartum period is also marked by dramatic shifts at corporal, mental and social levels in a woman's life including but not limited to hormonal swings and nervewracking parenting tasks that can cause women to experience stress and fatigue [3]. The physiological changes that can be seen during pregnancy include modifications in neuroendocrine hormonal shifts, inflammatory, and autonomic nervous system activation, which has the potential to aggravate the stress response and intensify the peril of perinatal physiological and psychological difficulties of the women [6]. Hence, as a distinct susceptible group, pregnant and postpartum women become high-end prey to stress and other such mental illness [4].…”
Section: Introductionmentioning
confidence: 99%
“…Stress can be understood as the responses one gives at the mental, emotional, and physiological levels to the demands of life [5]. However, how stress is experienced and understood by an individual depends on their preconceived perceptions, existing coping mechanisms, and their previous interactions with the environment rather than the stress-causing stimuli itself [6]. Postpartum maternal stress is usually connected with poor health outcomes and the advancement of psychological problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research shows that mothers who gave birth during the pandemic had more clinically acute stress responses in comparison to those who had children in previous years [ 3 , 4 , 5 ]. In turn, higher levels of stress during birth were associated with more childbirth-related posttraumatic stress disorder (PTSD) symptoms and less bonding with the infant [ 3 ].…”
Section: Introductionmentioning
confidence: 99%